Fundamental Movement Skills and Health-Related Outcomes: A Narrative Review of Longitudinal and Intervention Studies Targeting Typically Developing Children. Issue 2 (March 2018) - Bremer, Emily; Cairney, John
Many children with typical development are highly sedentary, overweight/obese, and are deemed not ready for school at kindergarten entry. All of these concerns can be related to a lack of movement skill proficiency in this population. The purpose of this narrative review was to synthesize the literature examining the impact of movement skills on 5 areas of overall health: physical activity, physical fitness, body composition, self-beliefs, and executive functioning. To gain an understanding of these relationships, only studies employing an experimental or observational longitudinal design were reviewed. Although the results were limited in the number of studies available, there is evidence that movement skill may have a positive influence on these broad domains of health both naturally over the course of development and through intervention. We recommend that a universal approach to movement skill development is warranted, given the range of benefits that stem from developing proficiency in these skills.